Designing and implementing maker curriculum for promoting 7th graders’ maker competence - Wu, Su-Chiao; Chang, Yu-Liang (Frontiers in Education, 2023)
“Competence” is a very important concept in education and has been valued by many countries and international organizations in recent years, which has sparked a wave of curriculum reform around the world. The STEAM education are considered as a feasible manner in equipping all students for problem solving skills in various real-world situations and complicated challenges, as well as nurturing them 21st century skills and competencies. Moreover, a recent maker movement that focuses more on hands-on, creation, design and innovation is considered as an innovative way to rethink how to redefine the learning process where students’ maker competence can be nurtured. Grounded on this curriculum reform trend, new national curriculum guidelines were established in 2014 by Ministry of Education, Taiwan. Especially for the technology domain in the junior high school level (grade 7-9), “Life Technology” and “Information Technology” become requirements, where an interdisciplinary and competence-based maker curriculum needs to be developed. Based on this curriculum reform wave, we argue for the implementation of the targeted maker curriculum as a way to increase 7th-grade students’ maker competence. A post-test only quasi-experiment design was employed for gathering the data, where corresponding statistics were applied for the quantitative comparison. A total of 230 7th-graders from eight classes of the targeted junior high school participated in this study. Students in the experimental group received an interdisciplinary and competence-based maker curriculum as the intervention, which was designed and implemented with the support of the teacher professional development community and briefly presented in this paper. The quantitative findings revealed that targeted 7th-graders who receiving the experimental intervention possessed significantly superior maker competence than those who received regular technology courses. Based on the findings, the maker competence (i.e. knowledge, attitude, and skills), which can be fully established within the interdisciplinary and competence-based maker classrooms, were significantly favorable for helping targeted adolescents survive in this ever-changing and fast-paced era. Consequently, we, as teacher educators and teachers, must endeavor to redefine the way of learning and construct a learning environment that is full with the maker spirit and STEAM integration.